Peran Kepala Sekolah Terhadap Kedisiplinan Guru di Madrasah Tsanawiyah Darunnajah 2 Cipining Bogor - Munfidah, Ahsani (Indo-MathEdu Intellectuals Journal, 2024)
The reason of this consider is to discover out how the principal's part contributes to progressing educator teach at Madrasah Tsanawiyah Darunnajah 2 Cipining Bogor. and to discover out the part of the school foremost in moving forward instructor teach at Madrasah Tsanawiyah Darunnajah 2 Cipining Bogor. The inquire about strategy utilized is graphic subjective with investigate disobedient utilized are meet guides, documentation, and information collection methods utilized incorporate interviews and documentation. subjective inquire about strategies. The center of this investigate is the part of the vital and instructor teach at Madrasah Tsanawiyah Darunnajah 2 Cipining Bogor. The comes about of the ponder are that the part of the school central in expanding educator teach has been realized to work well since of the favors of the principal's direction and inspiration towards instructors additionally from the mindfulness of the instructor himself in carrying out the order and duty as an teacher who ought to be an case and part demonstrate for his understudies , This ponder utilized subjective inquire about strategies. The center of this inquire about is the part of the vital and educator teach at Madrasah Tsanawiyah Darunnajah 2 Cipining Bogor.